Makna Insecurity, Video Klip, dan Generasi Z - Patricia, Cherryes; Utami , Lusia Savitri Setyo (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Feeling insecure is a natural thing experienced by every individual. The feelings of insecurity faced by Generation Z encouraged musicians to convey their message through one of (G)I-DLE's 'Allergy' video clips. The video clip 'Allergy' tells about feeling inferior and wanting to follow life on social media. By using Roland Barthes' semiotic analysis, the researcher aims to find out and describe the representation of the meaning of insecurity in Generation Z through the video clip (G)I-DLE 'Allergy'. This research is descriptive with a qualitative research approach. The results of this research are a representation of the meaning of insecurity experienced by Generation Z, which includes a feeling of difficulty in achieving expectations of being like an